Opinions and Experiences of Male Nursing Students After Clinical Practices of Obstetrics and Gynecology Course - Merve ERTUĞRUL; Eda ŞAHİN (Atatürk University, 2021)
Aim: To determine the experiences and opinions of male nursing students after their clinical practice in obstetrics and gynecology course and to examine how the nursing profession is perceived by male nursing students, the reasons for choosing the profession, and the suggestions of male nursing students for the practice of obstetrics and gynecology. Method: The research was conducted by using a phenomenological research design, one of the qualitative research methods, with 14 students studying at a Faculty of Health Sciences Nursing Department in the Black Sea Region in the fall semester of 2019-2020. The data were collected with a personal information form and a semi-structured interview form. The interviews were obtained by the researcher using the face-to-face interview technique. The data were collected until the data saturation was reached and the data saturation was reached with 14 students. In the study, descriptive and descriptive interpretative analyzes of fundamental analysis, then content and discourse analysis of in-depth analysis were used. The information in the personal information form was evaluated by number, percentage, average, and standard deviation. Results: The average age of the students is 21.54 ± 1.55, 57.14% of them are healthcare relatives and 64.28% of them have chosen the nursing profession willingly. Three themes were determined as "Professional opinions", "Practical views" and "Practical suggestions". Four sub-themes were determined as "Abstract views", "Concrete opinions", "Positive opinions" and "negative opinions". Conclusion: While students integrated nursing with helping people, they considered it easy to be appointed as reasons for choosing the profession and earning money. It was determined that students and their relatives were the most influential part of their negative behaviours due to their inability to be active in the application areas due to their gender and a sense of privacy. In this course, they stated that in order to be more active and to learn the practices, there should be trainings in order to develop their skills in the laboratory before the clinical practice.